Avaliação do bagaço de malte como biossorvente do corante Amarelo Reafix B2R - Zanutto, Adriane (2016)
Textile industries use various dyes to add value and make their products more attractive, serving a wide range of customers. In the dyeing step occurs the adhesion of the dye, in aqueous solution, to the textile fiber. After dyeing occurs washings of the fabric where the ramining dye is discarded. For this disposal doesn’t cause damage to the enviroment, it is necessary to remove the dye as much as possible of the water. In a river, for example, the textile dyes can prejudice the sunlight transmission and compromise the oxygen comsuption in that place. An alternative to solve this problem is te biosorption, which uses a biomass as the main agent in the removal of an undesirable pollutant. The malt bagasse is a biomass generated in large quantities in industrial and artisanal production of beer, which is discarded or used as animal feed, because it degrades quickly and doesn’t have significant value. Thus, evaluated the potential of malt bagasse like biosorbent of a dye commonly used in industrial scale: Yellow Reafix B2R. The tests were performed in duplicate, batch process, controlling temperature, rotation and pH. Preliminary tests were conducted to ascertain if there is influence of pH on the adsorption band and removal of the dye, and if there is influence of granulometry of the beer residues in the biosorption. In both cases a significant influence was not detected. It was held a factorial design 2², to obtain the optimum operating parameters for the removal of dye in later tests, which are: pH 2 and 130 rpm. The kinetic test was performed with these parameters and temperature of 30 ºC, setting the equilibrium time of approximately 6 hours, with a removal greater than 93% of the dye. The kinetic model of pseudo-second order set for the data. By balancing test was observed that data set to the Langmuir isotherm. The thermodynamic parameters of the process expressed that it occurs spontaneous and favorably, endothermic form and there are changes in the beer residues structure during the process of sorption. Lastly, analyzed the interference of ionic strenght and other dye in the biosorption. It was found that higher the concentration os salts lower is the removal, and the removal is virtually the same with the dye mixture. The results comprove that the malt bagasse has great potential to be used in the treatment of textile effluents.